Affective and evaluative responses to pop music - North, Adrian; Hargreaves, David (Springer New York LLC, 1998)
From reviews published in the “serious” pop music press, twenty recordings were selected which had received consistently favourable appraisals on affective and evaluative bases. A further twenty recordings were selected on the basis of high levels of chart performance but a lack of critical acclaim. Sixty-four subjects rated representative excerpts of these recordings on 11-point scales of either liking or artistic merit. The results indicated significantly lower liking and artistic merit ratings of critically praised excerpts; a positive liking-artistic merit correlation; and some “fragmentation” between affective and evaluative responses. The apparent discrepancy between the attitudes of the music press and subjects' ratings is discussed in terms of the availability and sophistication of evaluation cues.